2021
DOI: 10.1007/s10272-021-0949-x
|View full text |Cite
|
Sign up to set email alerts
|

Why the COVID-19 Pandemic Could Increase the Corporate Saving Trend in the Long Run

Abstract: Given the global trend in corporate saving over the last decades, the COVID-19 crisis raises doubts about the persistence of companies’ saving behaviour due to the losses which have occurred in many companies caused by the isolation of households and by lockdowns. Before the pandemic, corporate net lending activities had been increasing for decades due to various factors ranging from the rise in uncertainty after the global financial crisis to the increased reliance on internal funding for research and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Data Sources and Sample Selection. Demary et al proposed that the pattern of companies during COVID-19 was similar to that observed after the financial crisis [6]. Considering the similarity between the epidemic and the 2008 financial crisis, this paper chooses Shanghai and Shenzhen A-share listed corporations from 2007 to 2015 as the initial samples, which can provide some reference for enterprise capital holding decisions under the epidemic situation.…”
Section: Empirical Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Data Sources and Sample Selection. Demary et al proposed that the pattern of companies during COVID-19 was similar to that observed after the financial crisis [6]. Considering the similarity between the epidemic and the 2008 financial crisis, this paper chooses Shanghai and Shenzhen A-share listed corporations from 2007 to 2015 as the initial samples, which can provide some reference for enterprise capital holding decisions under the epidemic situation.…”
Section: Empirical Designmentioning
confidence: 99%
“…Now, under the outbreak of novel coronavirus pneumonia, the companies' cash holding once again becomes the decisive factor for the development of companies. Demary et al found that similar to the pattern observed after the financial crisis, companies affected by the COVID-19 will strengthen capital corporate saving to better cope with future shocks [6]. Some scholars proposed that companies with abundant cash holdings can buffer against the outbreak of the COVID-19 epidemic [7], and Wieczorek-Kosmala took the tourism industry as an example and proved the importance of cash holding in resisting risks [8].…”
Section: Introductionmentioning
confidence: 96%
“…In such uncertain economic conditions, companies have faced challenges such as declining profits, liquidity constraints, and the need to continue paying employees, debtors, and suppliers despite reduced revenues, leading companies to maintain higher levels of working capital to fund their operational needs and ensure liquidity. Besides, to safeguard against future negative cash flow shocks and to address the limited access to credit for companies with higher default probabilities, firms tend to create and maintain larger liquidity buffers consisting of cash and short-term assets (Demary et al 2021). This focus on liquidity and cash management contributed to the higher net working capital ratios observed during the COVID-19 pandemic.…”
Section: The Results Of the Research Modelsmentioning
confidence: 99%
“…The effectiveness and efficiency of the company's operational activities depend highly on the decision to determine the amount of holdings. The COVID-19 pandemic changed the company's paradigm in backing up its funds, especially when there was a decrease in company revenue (Demary et al, 2021). Cash holdings are the main thing that needs to be considered so that the company can meet its operational expenses and maintain its liquidity.…”
Section: Theoretical Reviewmentioning
confidence: 99%